Perbandingan Dukungan Sumber Daya non Finansial di Puskesmas Salaman 1 dan Puskesmas Gamping 1 terhadap Pelaksanaan Spm Bidang Kesehatan - Efina Cahyani Fandi; Sunarto Sunarto (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2021)
ABSTRACTHealth is one of the concurrent affairs that must be fulfilled by the government. Based on the Peraturan Menteri Kesehatan No. 43 of 2016, minimum service standards (SPM) are provisions regarding the type and quality of basic services which are mandatory government affairs that are entitled to be obtained by every citizen minimally. SPM has 12 indicators where all these indicators should ideally reach the target of 100% as a minimum, but not all indicators can achieve 100% results. This can be caused by non-financial resource factors that have not been fulfilled. The aim of this study is to compare the factors of non-financial resources at the Puskesmas Salaman 1 and Puskesmas Gamping 1 in the implementation of the SPM in the health sector. The study was conducted with qualitative methods with a case study approach. The result show that the factors of non-financial resources in the Puskesmas Gamping 1 and Puskesmas Salaman 1 have been adequately fulfilled, but there are some obstacles experienced, namely excessive workload so that one person holds several programs, the quality of human resources is different, not all drug stocks and reagents provided so that it must procure itself, and so forth. This obstacle indirectly affected the achievement of minimum health service standart in Gamping 1 Puskesmas and Salaman 1 Puskesmas so that they could not reach the target.